ENGLISH TEACHERS’ CHALLENGES IN IMPLEMENTING MERDEKA CURRICULUM - Robiatul Aminah Hasibuan; Absharini Kardena (CV. Ulil Albab Corp, 2024)
This study investigated the challenges that found by English teachers in implementing Merdeka curriculum at MAS Al – Amin Mompang. This research is descriptive qualitative research. The data collected by using interview. The participants of the study was four English teachers at MAS Al – Amin Mompang. The findings of this study highlight the need for the Ministry of Education, Culture, Research, and Technology to provide more support and resources to teachers to facilitate the implementation of the Merdeka Curriculum. This includes providing training and guidance on how to teach using the new curriculum, as well as providing access to resources and infrastructure that support technology-enhanced learning.